Hormone therapy for genitourinary syndrome of menopause: reality and prospects - Mekan R. Orazov; Viktor E. Radzinsky; Evgeny D. Dolgov (LLC "MEDIAFORMAT", 2024)
Genitourinary syndrome of menopause still represents one of the most pressing unresolved issues of modern gynecology. High prevalence and the data suggesting a marked decline in the quality of life in general and sexual life in particular in patients of this cohort demonstrate the need to develop effective clinical management programs. The review provided considers the key aspects of genitourinary syndrome of menopause as a medical and social problem, reports modern approaches to clinical management in the wake of new international guidelines.